Studies on Cowpea Varietal Resistance to the Cowpea Flower and Pod Borer, Maruca Testulalis (Geyer) (Lepidoptera Pyralidae). - Echendu, Thank-God Nnamdi (Obafemi Awolowo University, 2014)
Several varieties of cowpea, Vigna unguiculata s.sp. unguiculata (L,) Walp., were screened for resistance to the cowpea flower and pod borer, Maruca testulalis (Geyer) using free-choice field trials, cohort tests in large screened cages and no-choice tests in the screenhouse and the laboratory. The damage potential of M. testulalis on Ife Brown cowpea was also studied using controlled infestations in order to establish a baseline infestation level that could be used to differentiate resistance effectively in no choice tests.